2010
DOI: 10.1021/jp1043255
|View full text |Cite
|
Sign up to set email alerts
|

Octanol-Triggered Self-Assemblies of the CTAB/KBr System: A Microstructural Study

Abstract: A micelle-vesicle transition induced by n-octanol C(8)OH was observed in an aqueous cetyltrimethylammonium bromide (CTAB)/potassium bromide (KBr) system. This transition was investigated by viscosity, rheology, dynamic light scattering (DLS), and direct imaging technique, cryo-transmission electron microscopy (cryo-TEM). Viscometry shows that the system underwent several morphological transitions with the increase in concentration of C(8)OH (regions I-IV). At low octanol concentration (region I), DLS analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…Sreejith et al [53] investigated the mixture of CTAB and C 8 OH in the presence of KBr (Fig. 2.4d) and observed a thermally-induced response for C 8 OH/CTAB molar ratios above ~0.25.…”
Section: Thermo-thickening Cationic Wlmsmentioning
confidence: 99%
“…Sreejith et al [53] investigated the mixture of CTAB and C 8 OH in the presence of KBr (Fig. 2.4d) and observed a thermally-induced response for C 8 OH/CTAB molar ratios above ~0.25.…”
Section: Thermo-thickening Cationic Wlmsmentioning
confidence: 99%
“…The lower homologues affect the water structure, while the penetration of higher ones outweighs the effect, resulting in an increase of both the micellar size and viscosity, hence promoting micellar transition. Thus, alcohols/amines with long chains are employed in industrial applications as they are potential candidates to induce a rich variety of microstructures [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…With increase in [CTAT], the maximum shis to lower 1-hexanol concentration. 49 In 30 mM CTAT, the viscosity directly decreases without showing any maximum. This may be due to a more compact packing of micelles at higher [CTAT] which does not allow 1-hexanol molecules to penetrate.…”
mentioning
confidence: 96%
“…A detailed study on formation of vesicles from CTAB micelles in the presence of KBr has been reported for 1-octanol and it was concluded that sudden drop in viscosity aer maximum is due to formation of vesicles. 49 It is well reported that 1-octanol increases the aggregation number by forming mixed micelles. 45,49 It is obvious from above observations that 1-hexanol and 1-octanol are capable of forming vesicles from single surfactant solution while ethanol and 1-butanol are not.…”
mentioning
confidence: 98%
See 1 more Smart Citation